On Cordelair–Greil Model about Electrophoretic Deposition. Issue 26 (26th May 2022) - Liu, Wenbo; Li, Yifei; Li, Depeng; Chen, Lixuan; Zhao, Jinyang; Liu, Pai; Sun, Xiao Wei; Wang, Guoping
Abstract: Electrophoretic deposition (EPD) is a facile technique to deposit quantum dots (QDs) films, which can be used as the color conversion layers for display applications. To better understand the EPD process, researchers have built many models of the EPD process. However, most of these models lack solid experimental support. Here, by adopting simple yet effective solvent engineering and well‐designed experiments, this study proves the Cordelair–Greil model on EPD processes. Moreover, some supplements about this model are made according to practical experiments. The experimental verification of the Cordelair–Greil model is a solid step toward revealing the dynamics of the EPD process. Furthermore, the formation of cracks in EPD deposited QD films is prevented through solvent engineering. This work proves that besides modifying the intrinsic properties of QDs, solvent engineering is also a simple, effective, and low‐cost way to study the EPD process and improve the QD film qualities deposited. Abstract : By solvent engineering, the stable state and the flocculated/coagulated (F/C) state of quantum dots (QDs) described in Greil et al.'s work can be achieved. By well‐designed experiments, electrophoretic deposition (EPD) processes described in the Cordelair–Greil model can be proven. With a better understanding of the EPD process, the crack problems of QD films deposited by EPD can be resolved by adding polyvinylpyrrolidone in the QDs suspension.